Family relations of Moche elite burials on the North Coast of Peru (~500 CE): Analyses of the Señora de Cao and relatives - Jeffrey Quilter; Kelly Harkins; Régulo Fanco Jordan; Erik Marsh; Gabriel Prieto; John Verano; Steven LeBlanc; Nasreen Broomandkhoshbacht; John Krigbaum; Lars Fehren-Schmitz (Proceedings of the National Academy of Sciences, 2025)
The Moche archaeological culture flourished along Peru’s North Coast between the 4th and 10th centuries CE and was characterized by a complex social hierarchy dominated by political and religious elites. Previous archaeological evidence suggests kinship was a key factor in maintaining political authority within Moche society. To test this hypothesis, we applied archaeological, genetic, and isotopic methods to examine familial relationships between six individuals, including the prominent Señora de Cao ( ~500 CE ), buried together in a pyramid-like, painted temple, Huaca Cao Viejo, in the Chicama Valley, Peru. Our findings reveal that all six individuals were biologically related, with varying degrees of kinship. The Señora de Cao was interred with a sacrificed juvenile, identified as a possible niece, and at least one, and potentially two siblings and a grandparent in separate tombs nearby. One of the male siblings was accompanied in death by his sacrificed son. Isotopic analysis indicates that while most individuals had diets rich in maize and animal protein and spent their childhoods in or near the Chicama Valley, the sacrificed juvenile accompanying the Señora had a distinct diet and geographic origin. These results demonstrate that Moche elites were interred with family members, including some raised far from their parental homes. This supports the hypothesis that kinship was central to transmitting status and authority. Moreover, sacrificing family members to accompany deceased elites underscores the significance of ritual sacrifice in reinforcing familial ties and linking the deceased to both ancestors and the divine.